ACCESS TO JUSTICE OF PLEA BARGAINING IN ADDRESSING THE CHALLENGE OF TAX CRIME IN INDONESIA - Andhy H. Bolifaar (Scientia Integritas Utama, 2022)
It is crucial and urgent to construct the prevailing law of plea bargaining in the x-factor to generate the ideal of plea bargaining in addressing the challenge of tax crime in Indonesia based on access to the justice concept. The purpose of this study is to show that the use of the normative juridical method is adequate in answering the formulation of existing problems and, at the same time, providing constructive suggestions for these legal issues. Several facts, such as the number of tax crimes and the amount of loss in state revenues that arise, indicate the need to consider law enforcement in the field of taxation with a sociological perspective, one of which is by producing a legal concept in plea bargaining in the taxation sector. Of course, the ideal tax enforcement in renewing plea bargaining in taxes is sufficient to use the idea of access to justice. It is necessary to study legal empiricism on direct taxpayers. However, this normative study can enrich the study of legal empiricism in subsequent research. Access to justice is ideal in building plea bargaining to handle the challenges of tax crimes in Indonesia. The building of the access to justice concept includes regulating taxpayers' good faith, granting taxpayer rights in plea bargaining, and updating the rules for criminal sanctions for fines at each stage of authority.